KURFA: STRATEGI PEMENUHAN PANGAN BERKELANJUTAN MELALUI PROGRAM KOLABORASI URBAN FARMING DESA ANDONGREJO - Juan Vincent Elfonda; Muhammad Syirojd Arvany; Adinda Dwi Putri; Fery Irawan; Fakhruddin Mutakin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Indonesia is a country that has potential in the agricultural sector. Andongrejo Village, which is part of Tempurejo District, is one of the areas that makes the agricultural sector the main livelihood activity. The constraints faced by the community are limited water resources which cause the planting season to only be carried out two periods in a year. This is the background to the creation of the Andongrejo Urban Farming Collaboration (KURFA) work program. KURFA includes activities to socialize work programs and cultivation guides, cultivation practices, monitoring and socialization of the sustainability of planted products. The target of KURFA activities is 18 Housewives (IRT) who are members of the Andongrejo Village Women's Farmer Group (KWT). The KURFA work program aims to increase independent food fulfillment and encourage the community's economy through direct distribution of crops or through processed product innovation.